Using the Semantic Mapping Technique in Improving Students’ Writing Procedure Text at Vocational High School - Yudi Christo; Muhamad Yahrif; Sujarwo (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2026)
This research aimed to investigate the effectiveness of the Semantic Mapping Technique in improving students’ writing ability of procedure text at a vocational high school. This research employed a quantitative method using a quasi-experimental design involving an experimental class and a control class. The population of this research consisted of tenth-grade students at SMK Darussalam Makassar in the academic year 2025/2026. The sample consisted of 42 students divided into two classes, namely 21 students in the experimental class and 21 students in the control class. The instrument used was a writing test in the form of a pre-test and a post-test. The data were analyzed using descriptive and inferential statistics with the assistance of SPSS version 25. The results showed that the mean score of the experimental class improved from 70.24 in the pre-test to 91.00 in the post-test, while the control class improved from 76.05 to 84.10. The result of the independent samples t-test showed that the significance value (Sig. 2-tailed) was lower than 0.05, indicating that there was a significant difference between students taught using the Semantic Mapping Technique and those taught using conventional teaching techniques. Therefore, the Semantic Mapping Technique was effective in improving students’ writing ability of procedure text, particularly in organizing ideas, arranging procedural steps systematically, and developing vocabulary.